The Clinical Utility of Point-of-Care Tests for Influenza in Ambulatory Care: A Systematic Review and Meta-analysis. (4th October 2018) - Lee, Joseph Jonathan; Verbakel, Jan Y; Goyder, Clare Rosemary; Ananthakumar, Thanusha; Tan, Pui San; Turner, Phillip James; Hayward, Gail; Van den Bruel, Ann
Abstract : We reviewed the evidence for the impact of point-of-care diagnostic tests for influenza. Testing reduced further investigation with chest radiography and full blood counts, and increased antiviral prescribing, but had no impact on antibiotic use, returning for care, or admissions. Abstract: Background: Point-of-care tests (POCTs) for influenza are diagnostically superior to clinical diagnosis, but their impact on patient outcomes is unclear. Methods: A systematic review of influenza POCTs versus usual care in ambulatory care settings. Studies were identified by searching six databases and assessed using the Cochrane risk of bias tool. Estimates of risk ratios (RR), standardised mean differences, 95% confidence intervals and I2 were obtained by random effects meta-analyses. We explored heterogeneity with sensitivity analyses and meta-regression. Results: 12, 928 citations were screened. Seven randomized studies (n = 4, 324) and six non-randomized studies (n = 4, 774) were included. Most evidence came from paediatric emergency departments. Risk of bias was moderate in randomized studies and higher in non-randomized studies. In randomized trials, POCTs had no effect on admissions (RR 0.93, 95% CI 0.61–1.42, I2 = 34%), returning for care (RR 1.00 95% CI = 0.77–1.29, I2 = 7%), or antibiotic prescribing (RR 0.97, 95% CI 0.82–1.15, I2 = 70%), but increased prescribing of antivirals (RR 2.65, 95% CI 1.95–3.60; I2 = 0%). Further testing was reduced for full blood counts (FBC) (RR 0.80, 95% CI 0.69–0.92 I2 = 0%), blood cultures (RR 0.82, 95% CI 0.68–0.99; I2 = 0%) and chest radiography (RR 0.81, 95% CI 0.68–0.96; I2 = 32%), but not urinalysis (RR 0.91, 95% CI 0.78–w1.07; I2 = 20%). Time in the emergency department was not changed. Fewer non-randomized studies reported these outcomes, with some findings reversed or attenuated (fewer antibiotic prescriptions and less urinalysis in tested patients). Conclusions: Point-of-care testing for influenza influences prescribing and testing decisions, particularly for children in emergency departments. Observational evidence shows challenges for real-world implementation.